2016
DOI: 10.1371/journal.pone.0154694
|View full text |Cite
|
Sign up to set email alerts
|

Association between Image Characteristics on Chest CT and Severe Pleural Adhesion during Lung Cancer Surgery

Abstract: The aim of this study was to investigate the association between image characteristics on preoperative chest CT and severe pleural adhesion during surgery in lung cancer patients. We included consecutive 124 patients who underwent lung cancer surgeries. Preoperative chest CT was retrospectively reviewed to assess pleural thickening or calcification, pulmonary calcified nodules, active pulmonary inflammation, extent of emphysema, interstitial pneumonitis, and bronchiectasis in the operated thorax. The extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…It was found that the two groups of pediatric patients were significantly different in terms of operation time, intraoperative blood loss, postoperative length of hospital stay, postoperative drainage volume, and exposure to the operative field ( P < 0.05). Our results agreed with Chen et al [ 17 ], confirming that the central venous catheterization did shorten the length of hospital stay. The probable reason is that it is easier to perform central venous catheterization and a syringe can be connected to the catheter to aid the suction in case of inadequate drainage.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the two groups of pediatric patients were significantly different in terms of operation time, intraoperative blood loss, postoperative length of hospital stay, postoperative drainage volume, and exposure to the operative field ( P < 0.05). Our results agreed with Chen et al [ 17 ], confirming that the central venous catheterization did shorten the length of hospital stay. The probable reason is that it is easier to perform central venous catheterization and a syringe can be connected to the catheter to aid the suction in case of inadequate drainage.…”
Section: Discussionsupporting
confidence: 93%
“…For patients who had undergone pulmonary surgery, the tumor motion was significantly smaller in the CC and 3D directions than for patients without pulmonary surgery ( p = 0.024 and 0.015, respectively), which may be associated with pulmonary inflammation, tissue adhesion, 33 and lung volume reduction after pulmonary surgery. The tumor motion for these patients is more unpredictable and is poorly associated with the tumor location and clinical factors.…”
Section: Discussionmentioning
confidence: 91%
“…The CT findings of pleural calcification and parenchymal calcified nodule were also evaluated as image characteristics for predicting pleural adhesion and subsequent conversion. Pleural calcification was defined as any calcification at the pleural area on the axial images of unenhanced CT. Any size of parenchymal nodule containing calcification o n t h e u n e n h a n c e d C T i m a g e s w a s r e g a r d e d a s parenchymal calcified nodule, regardless of the shape of calcification (16,17). Calcification was defined as the attenuation above 200 HU and measured in mediastinal window setting (window with, 400 HU; window center, 30 HU).…”
Section: Image Interpretationmentioning
confidence: 99%